PENGARUH SUHU DAN LAMA WAKTU PENYIMPANAN TERHADAP AKTIVITAS ANTIMIKROBIA, SIFAT KIMIA DAN FISIK KERTAS AKTIF YANG MENGANDUNG SINAMALDEHIDA - , GODRAS JATI MANUHARA, Dr. Ir. Supriyadi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Active paper made from pulp and chitosan mixture with the incorporation of cinnamaldehyde still need further investigation. This study was designed to determine the effect of temperature (10, 20, 25, 30, and 40Â°C) during 20 day sof storage on antimicrobial activity, chemical properties (antioxidant activitiy, water and cinnamaldehyde content)